PENGGUNAAN KATA TUGAS DALAM TEKS EKSPOSISI SISWA KELAS VII SMP NEGERI 2 BUKITTINGGI - Pratami, Intan; Emidar, Emidar; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ The purpose of this research is to discribe the using of preposition and conjunction in the expotition text as class VII at SMP Negeri 2 Bukittinggi. The type of this research is qualitative research with descriptive method. The result of this research is found that the using of preposition that is states of meaning of whex a place, direction from, purpose direction, comparison, subject, and restriction. The conjunction that is which used are intra-sentence conjunction and antar-sntence conjunction. The student still can not using preposition and conjunction correctly.Â Kata kunci : kata tugas, preposisi, konjungtor